A note on vanishing Morrey -> VMO result for fractional integrals of variable order - Rafeiro, Humberto (2021)
In the limiting case of Sobolev-Adams theorem for Morrey spaces of variable order we prove that the fractional operator of variable order maps the corresponding vanishing Morrey space into VMO.